Voluntary Counseling and Testing (Vct) to Prisoner in Class I Prison of Surabaya - Abdul Muhith; Linda Prasetyaning; Nursalam Nursalam (Jurnal Ners, 2012)
Introduction: VCT is one of the efforts of the prison to minimize the risk of HIV/AIDS on Injecting Drug User Prisoners. But there are still obstacles in the implementation of this program in prison. The purpose of this study was to evaluate the VCT in Class I Surabaya Prison.Method: This study used qualitative and quantitative method. Samples to evaluate the VCT Program among Ofﬁ cer, Clinical Ofﬁcers who carry out VCT and NGOs as well as four IDU prisoners selected using purposive sampling. Samples to describe prisoner's characteristic and risk factor of HIV/AIDS from behavior aspect were 60 prisoners. Data were collected by ﬁlling out the questionnaire and in depth interview.Result: The results were analyzed by qualitative descriptive narrative. The results of this study was a major behavioral factors that lead to the incidence of HIV/AIDS on injecting drug user prisoners, unsafe sexual behavior and tattooing.Discussion: As for the evaluation of VCT was not performed well. In terms of input, the human resources sector and source of funds and independent laboratory facilities were deemed less. On process aspects, the sector of pre-and post-test counseling and support programs was still not optimal. In the aspect of output, an indicator to measure the success of VCT, patient satisfaction questionnaire coverage and effort to VCT client was still not implemented. It is necessary to enhance the implementation of VCT and to realize a program especially for drug user prisoners to prevent and control the transmission of HIV/AIDS such as harm reduction program.